Controlled Bipolar Doping of One-Dimensional van der Waals Nb2Pd3Se8 - Jeong, Byung Joo; Lee, Bom; Choi, Kyung Hwan; Sung, Dongchul; Ghods, Soheil; Lee, Junho; Jeon, Jiho; Cho, Sooheon; Lee, Sang Hoon; Kim, Bum Jun; Kim, Seung Il; Huh, Joonsuk; et al. (Nano Letters, 2023)
Tailoring the electrical properties of one-dimensional (1D) van der Waals (vdW) materials is desirable for their applications toward electronic devices by exploiting their unique characteristics. However, 1D vdW materials have not been extensively investigated for modulation of their electrical properties. Here we control doping levels and types of 1D vdW Nb2Pd3Se8 over a wide energy range by immersion in AuCl3 or β-nicotinamide adenine dinucleotide (NADH) solutions, respectively. Through spectroscopic analyses and electrical characterizations, we confirm that the charges were effectively transferred to Nb2Pd3Se8, and the dopant concentration was adjusted to the immersion time. Furthermore, we make the axial p-n junction of 1D Nb2Pd3Se8 by a selective area p-doping using the AuCl3 solution, which exhibits rectifying behavior with an Iforward/Ireverse of 81 and an ideality factor of 1.2. Our findings could pave the way to more practical and functional electronic devices based on 1D vdW materials.
Keywords: 1d van der waal material; Chemical doping; Doping levels; Electronics devices; Field-effect transistor; NADH; One-dimensional; Van der Waal; Wide energy range; β-nicotinamide adenine dinucleotide; 1D van der Waals material; AuCl3; Chemical doping; Field-effect transistor; NADH; Nb2Pd3Se8